Chemopreventive effect of cactus Opuntia ficus indica on oxidative stress and genotoxicity of aflatoxin B1 - Brahmi, Dalel; Bouaziz, Chayma; Ayed, Yousra; Ben Mansour, Hédi; Zourgui, Lazhar; Bacha, Hassen (Nutrition & metabolism, 2011)
Background Aflatoxin B1 (AFB1) is potent hepatotoxic and hepatocarcinogenic agent. In aflatoxicosis, oxidative stress is a common mechanism contributing to initiation and progression of hepatic damage. The aim of this work was to evaluate the hepatoprotective effect of cactus cladode extract (CCE) on aflatoxin B1-induced liver damage in mice by measuring malondialdehyde (MDA) level, the protein carbonyls generation and the heat shock proteins Hsp 70 and Hsp 27 expressions in liver. We also looked for an eventual protective effect against AFB1-induced genotoxicity as determined by chromosome aberrations test, SOS Chromotest and DNA fragmentation assay. We further evaluated the modulation of p53, bax and bcl2 protein expressions in liver. Methods Adult, healthy balbC (20-25 g) male mice were pre-treated by intraperitonial administration of CCE (50 mg/Kg.b.w) for 2 weeks. Control animals were treated 3 days a week for 4 weeks by intraperitonial administration of 250 μg/Kg.b.w AFB1. Animals treated by AFB1 and CCE were divided into two groups: the first group was administrated CCE 2 hours before each treatment with AFB1 3 days a week for 4 weeks. The second group was administrated without pre-treatment with CCE but this extract was administrated 24 hours after each treatment with AFB1 3 days a week for 4 weeks. Results Our results clearly showed that AFB1 induced significant alterations in oxidative stress markers. In addition, it has a genotoxic potential and it increased the expression of pro apoptotic proteins p53 and bax and decreased the expression of bcl2. The treatment of CCE before or after treatment with AFB1, showed (i) a total reduction of AFB1 induced oxidative damage markers, (ii) an anti-genotoxic effect resulting in an efficient prevention of chromosomal aberrations and DNA fragmentation compared to the group treated with AFB1 alone (iii) restriction of the effect of AFB1 by differential modulation of the expression of p53 which decreased as well as its associated genes such as bax and bcl2. Conclusion We concluded that CCE might have a hepatoprotective effect against aflatoxicosis in mice, probably acting by promoting the antioxidant defence systems.